HUBUNGAN ANTARA SELF-ESTEEM DAN PERILAKU ACADEMIC DISHONESTY MAHASISWA FIP UNNES DENGAN MEDIATOR PEER PRESSURE (Intuisi : Jurnal Psikologi Ilmiah, 2009)
The research is aimed at examining the correlation between self-esteem and academic dishonesty behavior mediated by peer pressure, as proposed hipothesis. The subject of this research were 212 students of FIP UNNES graduation of  2006 to 2008. Sampling technique which is used is stratified proportional random sampling. The data collection was done using academic dishonesty behavior questionnaire, self-esteem scale, and peer pressure scale. Hypothesis is tested by mediator analysis. The result indicate that there was significant correlation between self-esteem dan academic dishonesty behavior mediated by peer pressure (b= -0,1173, p0,05) at FIP UNNES students. Low peer pressure will lower academic dishonesty behavior and the opposite.